Penyelesaian Perceraian Yang Dilakukan Di Luar Pengadilan Studi Kasus Di Desa Mudung Darat Kecamatan Maro Sebo Kabupaten Muaro Jambi - Maryati, Maryati; Puspita, Sriayu Indah; Rostarum, Triamy; Sari, Mayang (Wajah Hukum, 2023)
Regarding the settlement of divorce outside the court, it is not something new, but there are many problems related to marriages that were carried out previously. According to the provisions of the marriage law, divorce should be carried out in a court session, and not outside the court session, This is what makes me interested in exploring divorce cases that are carried out outside of court, the impact of a divorce that is carried out outside of court, for the wife, especially not only on the wife's rights but also regarding the rights of children and joint property that they acquired during the marriage. not obtained by the wife and their children, if during the marriage they obtained children and property. However, the divorce carried out by this husband and wife couple is not the same as marriage in general, where the implementation of the marriage carried out by both parties is carried out in Mudung Darat Village, Maro Sebo District, Muaro Jambi Regency in a private manner or privately, and witnessed. by local traditional leaders, the divorce cannot be carried out in court, only traditional leaders can finalize the divorce from the couple, besides that the woman (ex-wife) does not get any rights at all towards her husband.